Seroprevalence of Hepatitis B and C in Coronary Artery Disease Patients in Urmia, Northwest of Iran - Rostamzadeh Khameneh, Zakieh (Archives of Medical Laboratory Sciences, 2020)
Background: Coronary artery disease (CAD) is one of the main causes of death all over the world. Predisposing factors comprise some infectious etiologies with systemic effects such as the hepatitis C virus and HBV-infection might be related to CAD from chronic inflammation process. The relationships between hepatitis B and C virus (HBV and HCV) infections and CAD considered a noticeable health problem. In the present study, we evaluated the seropositivity of HCV and HBV in CAD patients from the Iranian population. Materials and Methods: We conducted a cohort study including 192 CAD subjects. To identify HCV and HBV -infected subjects, a serologic examination comprising Hepatitis B surface antigen (HBsAg) and anti-HCV antibodies (HCV-Ab) tests performed by ELISA method. Also, we examined the biochemical blood parameters such as lipid profile, glycemic parameters, and blood inflammatory factor (C-reactive protein). Results: We identified a very low percent of HBV-infected cases (1.04%). All examined CAD patients indicate the HCV Ab-negative results. The HBV-infected subject had not, hyperlipidemia, and diabetes. HBV infection was not related to the increased risk of CAD. Also, CAD risk factors were not associated with the prevalence of HBV and HCV. Conclusion: According to the results, HCV and HBV infections had very low prevalence in examined subjects and there was not any association between CAD and prevalence of HCV and HBV infections.